Molecular Ultrasound Imaging for the Detection of Neural Inflammation: A Longitudinal Dosing Pilot Study. (November 2017) - Volz, Kevin R.; Evans, Kevin D.; Kanner, Christopher D.; Buford, John A.; Freimer, Miriam; Sommerich, Carolyn M.; Basso, D. Michele
Molecular ultrasound imaging provides the ability to detect physiologic processes noninvasively by targeting a variety of biomarkers in vivo. The current study was performed by exploiting an inflammatory biomarker, P-selectin, known to be present following spinal cord injury. Using a murine model (n = 6), molecular ultrasound imaging was performed using contrast microbubbles modified to target and adhere to P-selectin, prior to spinal cord injury (0D), acute stage postinjury (7D), and chronic stage (42D). Additionally, two imaging sessions were performed on each subject at specific time points, using doses of 30 μL and 100 μL. Upon analysis, targeted contrast analysis parameters were appreciably increased during the 7D scan compared with the 42D scan, without statistical significance. When examining the dose levels, the 30-μL dose demonstrated greater values than the 100-μL dose but lacked statistical significance. These findings provide additional preclinical evidence for the use of molecular ultrasound imaging for the possible detection of inflammation.